Other People: a child's age predicts a source's effect on memory - Carol, Rolando N. (Legal and criminological psychology, 2017)
Purpose. For decades, researchers have investigated the effects of various interviewing techniques used in child witness interviews. One particular technique yet to be explored fully is Other People, that is, mentioning other witnesses’ alleged statements when interviewing a child. This study thus examined how the source of others’ information affects children's memory and source monitoring as a function of age (7–18). Method. Children and adolescents (N = 110) watched a 10-min video and were then questioned about the witnessed event 1 week later using a series of yes/no questions. Throughout this series of questions, the source of outside information (peer vs. adult vs. no source) and its veracity (correct vs. incorrect) were manipulated. Results. Findings indicated that an adult source was more detrimental to witness accuracy than a peer source or no source, but this detrimental effect diminished as witness age increased. Source monitoring data mirrored this pattern: As age increased, so did accurate source attributions for information attributed to an adult. Conclusion. Overall findings suggest that information source in conjunction with witness age should be considered when assessing the effect of outside information on child and adolescent memory.